2012
DOI: 10.1111/j.1525-1470.2012.01874.x
|View full text |Cite
|
Sign up to set email alerts
|

Dermoscopy for the Pediatric Dermatologist, Part II: Dermoscopy of Genetic Syndromes with Cutaneous Manifestations and Pediatric Vascular Lesions

Abstract: Genetic syndromes including basal cell nevus syndrome (BSNS), xeroderma pigmentosum (XP), and epidermodysplasia verruciformis (EV) predispose the individual to skin cancer. Basal cell carcinomas (BCCs) often develop in patients with BCNS and XP. One of the aims of surveillance examination in these patients is to detect BCC while the tumors are still small and easy to manage. Dermoscopy, by allowing the visualization of arborizing vessels, ovoid nests, nonaggregated blue-gray globules, and spoke-wheel and leaf-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0
12

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 52 publications
0
30
0
12
Order By: Relevance
“…The color of the vesicles ranges from clear to red or blueblack depending on the amount of blood content. Dermoscopy is very helpful to differentiate lymphangioma circumscriptum from other vascular lesions such as hemangioma, angiokeratoma, lymphangioendothelioma and angiosarcoma [2,3]. Lymphangioma circumscriptum is characterized by a lacunar pattern surrounded by paler septa, skin-colored to yellow globules next to red or blue-black globules caused by blood.…”
Section: Discussionmentioning
confidence: 99%
“…The color of the vesicles ranges from clear to red or blueblack depending on the amount of blood content. Dermoscopy is very helpful to differentiate lymphangioma circumscriptum from other vascular lesions such as hemangioma, angiokeratoma, lymphangioendothelioma and angiosarcoma [2,3]. Lymphangioma circumscriptum is characterized by a lacunar pattern surrounded by paler septa, skin-colored to yellow globules next to red or blue-black globules caused by blood.…”
Section: Discussionmentioning
confidence: 99%
“…Since characteristics of basal cell carcinomas of NBCCS do not differ from characteristics of sporadic ones, it is not unpredictable to detect typical dermoscopic features including spoke-wheel areas, maple-leaf like areas, blue grey ovoid nests and ulceration in basal cell carcinomas of NBCCS. [13][14][15][16][17][18][19][20] Moreover, it has been suggested that maple leaflike areas, short fine superficial telangiectasia, multiple small erosions, and shiny white-red structureless areas seem to be potent predictors of superficial basal cell carcinomas, whereas the presence of arborizing vessels, blue grey ovoid nests and ulceration seem to be related with non-superficial basal cell carcinomas of NBCCS. 19 We have also confirmed these findings and demonstrated that dermoscopic features of the pigmented nodule on the abdominal region of the patient included multiple large blue grey ovoid nests, arborizing vessels and an ulceration.…”
Section: Figurementioning
confidence: 99%
“…Dermoscopy is helpful not only in the early detection of basal cell carcinomas of NBCCS, but also in the management of the affected patients. [13][14][15][16][17][18][19][20] We suggest that further reports and studies are needed on the dermoscopic findings of basal cell carcinomas of NBCCS.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations